2009
DOI: 10.2337/dc09-0114
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia Unawareness in Older Compared With Middle-Aged Patients With Type 2 Diabetes

Abstract: OBJECTIVEOlder patients with type 2 diabetes are at a particularly high risk for severe hypoglycemic episodes, and experimental studies in healthy subjects hint at a reduced awareness of hypoglycemia in aged humans. However, subjective responses to hypoglycemia have rarely been assessed in older type 2 diabetic patients.RESEARCH DESIGN AND METHODSWe tested hormonal, subjective, and cognitive responses (reaction time) to 30-min steady-state hypoglycemia at a level of 2.8 mmol/l in 13 older (≥65 years) and 13 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
164
2
20

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(192 citation statements)
references
References 10 publications
(18 reference statements)
0
164
2
20
Order By: Relevance
“…Estas observaciones, sumadas a los recientes reportes de aumento en la mortalidad de diabéti-cos tipo 2 manejados bajo esquemas terapéuticos orientados al logro de niveles de Hb glicosilada A1C < 6% 17 , sugieren considerar una mayor flexibilidad en las metas de control metabólico, especialmente en el subgrupo de adultos mayores 18 .…”
Section: Discussionunclassified
“…Estas observaciones, sumadas a los recientes reportes de aumento en la mortalidad de diabéti-cos tipo 2 manejados bajo esquemas terapéuticos orientados al logro de niveles de Hb glicosilada A1C < 6% 17 , sugieren considerar una mayor flexibilidad en las metas de control metabólico, especialmente en el subgrupo de adultos mayores 18 .…”
Section: Discussionunclassified
“…The significant number of cases of hypoglycaemia results from the unnecessary use of drugs associated with an increased risk of hypoglycaemia, especially in old patients with advanced co-morbidities [18]. Moreover, a combination of cognitive dysfunction and hypoglycaemic unawareness, which is clearly noticed more frequently in the elderly, is a critical factor in the treatment of this age group [19].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced hypoglycemia might also be expected to improve adherence to the IDegAsp insulin regimen [26], although (as yet) no data have been found that are related to fear of hypoglycemia or health-related quality of life. Reduction in nocturnal hypoglycemia can also be expected to reduce the problem of hypoglycemia awareness, something that becomes more common in middle and later age [57] but, again, no data are yet available on this issue for IDegAsp.…”
Section: Five-year Viewmentioning
confidence: 99%